The university revisited: a journey of discovery / Corporate Communications & International Relations Office, UiTM - UiTM, Corporate Communications & International Relations Office (Corporate Communications & International Relations Office, UiTM, 2006)
The University Revisited. A Journey of Discovery is an account of a special tour of Universiti Teknologi MARA (UiTM), one of the oldest and biggest universities in Malaysia. The journey takes a closer look at UiTM through a different set of eyes that will experience a fresh new perspective of the university. To do this, you have to go along a road that is less travelled, a road portraying another side to the university that very few people know or are even aware of. It offers a new insight of the university's role, a role imbued with all the human qualities necessary to take its community of students and staff towards a world-class university status with a difference.